Strategi Humas Dinas Pariwisata Kota Banda Aceh Dalam Membangun Banda Aceh Sebagai Kota Pariwisata: (Studi Pada Dinas Pariwisata Banda Aceh) - Zakirah Azman; Mohd Arif Maulana; Rahmat Saleh (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2019)
This research was titled "PR Strategy of tourism Office of Banda Aceh in building Banda Aceh as Tourism city". The theory used is theory of planning. This research is qualitative research with descriptive type. There are 5 informant in this study. The data collection methods used are interviews, observations, and documentation. Based on the research that has been done, the results of the strategy that was conducted in the promotion process of Banda Aceh as a tourism city is ranging from the annual program of Chairming Kota Banda ACEH, doing cooperation with City District government in the vicinity of Banda Aceh, doing cooperation with travel-travel both at the Regional, national and international level, as well as promoting through social media Instagram and also the use of the official website To provide information about tourism in the city of Banda Aceh. Constraints such as the lack of understanding of the community around the location of the tourist objects from the positive value of the location of tourist objects, there are still public statmen to the condition of Banda Aceh resulting from the history of conflict In Aceh.